Surrogate fostering of mice prevents prenatal estradiol-induced insulin resistance via modulation of the microbiota-gut-brain axis - Wang, Huihui; Zhou, Chengliang; Gu, Shuping; Sun, Yun (Frontiers in Microbiology, 2023)
Prenatal and early postnatal development are known to influence future health. We previously reported that prenatal high estradiol (HE) exposure induces insulin resistance in male mice by disrupting hypothalamus development. Because a foster dam can modify a pup’s gut microbiota and affect its health later in life, we explored whether surrogate fostering could also influence glucose metabolism in HE offspring and examined mechanisms that might be involved. HE pups raised by HE foster dams (HE-HE) developed insulin resistance, but HE pups fostered by negative control dams (NC-HE) did not. The gut microbiota composition of HE-HE mice differed from that of NC mice raised by NC foster dams (NC-NC), whereas the composition in NC-HE mice was similar to that of NC-NC mice. Compared with NC-NC mice, HE-HE mice had decreased levels of fecal short-chain fatty acids and serum intestinal hormones, increased food intake, and increased hypothalamic neuropeptide Y expression. In contrast, none of these indices differed between NC-HE and NC-NC mice. Spearman correlation analysis revealed a significant correlation between the altered gut microbiota composition and the insulin resistance-related metabolic indicators, indicating involvement of the microbiota-gut-brain axis. Our findings suggest that alterations in the early growth environment may prevent fetal-programmed glucose metabolic disorder via modulation of the microbiota-gut-brain axis.